2015
DOI: 10.1016/j.expneurol.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

MFGE8/Integrin β3 pathway alleviates apoptosis and inflammation in early brain injury after subarachnoid hemorrhage in rats

Abstract: Background Milk fat globule-epidermal growth factor-factor 8(MFGE8)/Integrin β3 pathway was reported to be involved in reducing oxidative stress and early brain injury after Subarachnoid Hemorrhage (SAH). In the present study, the potential effects of MFGE8 and its receptor Integrin β3 in the inhibition of apoptosis and neuroinflammation in early brain injury after SAH were investigated. Methods Ninety-five (95) male Sprague-Dawley rats were used. The SAH model was induced by endovascular perforation. Recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 53 publications
1
37
0
Order By: Relevance
“…EGFR (epidermal growth factor receptor) and ASCL1 (achaete-scute homolog1) are indeed commonly used markers for C cells. MFGE8 (milk fat globule-epidermal growth factor-8) and its receptor β3 integrin (Itgb3) are known to induce phagocytosis of apoptotic cells and to act as "endogenous protective factors" in response to various brain lesions (Deroide et al 2013, Liu et al 2015, Xiao et al 2018. We found β3 Integrin expressed in most of the microglial cells present in the demyelinated CC (Suppl Fig 2C).…”
Section: Identification Of Ligand-receptor Couples Involved In the DImentioning
confidence: 69%
“…EGFR (epidermal growth factor receptor) and ASCL1 (achaete-scute homolog1) are indeed commonly used markers for C cells. MFGE8 (milk fat globule-epidermal growth factor-8) and its receptor β3 integrin (Itgb3) are known to induce phagocytosis of apoptotic cells and to act as "endogenous protective factors" in response to various brain lesions (Deroide et al 2013, Liu et al 2015, Xiao et al 2018. We found β3 Integrin expressed in most of the microglial cells present in the demyelinated CC (Suppl Fig 2C).…”
Section: Identification Of Ligand-receptor Couples Involved In the DImentioning
confidence: 69%
“…27 MFG-E8/integrin β3 may be involved in neuroinflammation and apoptotic changes after SAH. 24 It also has been reported that integrin β3 regulated the expression of Th2 cytokines in the rejecting transplant. 28 In addition, β3 integrin plays a critical role in vascular development/maturation and regulating the vascular sensitivity to VEGF in the heart.…”
Section: Discussionmentioning
confidence: 96%
“…Several recent studies have confirmed the therapeutic potential of MFG-E8 in various renal diseases, such as renal ischemiareperfusion injury and sepsis-induced acute kidney disease [51]. MFG-E8 has also been shown to protect the kidneys by suppressing inflammation and apoptosis [52,53]. Moreover, MFG-E8 plays an essential role in macrophage reprogramming through the induction of the anti-inflammatory M2 phenotype [19].…”
Section: Discussionmentioning
confidence: 97%